Amberlyst-15 supported zirconium sulfonate as an efficient catalyst for Meerwein–Ponndorf–Verley reductions. Issue 25 (9th March 2022) - Wang, Zixin; Xie, Chao; Li, Xun; Nie, Jiabao; Yang, Hanmin; Zhang, Zehui
Abstract : A new kind of sulfonate coordinated Zr(IV) catalyst was prepared by the coordination of Zr(IV) onto sulfonate groups of Amberlyst-15, which can effectively catalyze the MPV reaction and convert carbonyl compounds to the corresponding alcohols. Abstract : The Meerwein–Ponndorf–Verley (MPV) reaction is an important chemoselective route for carbonyl group hydrogenation, and thus designing new and effective catalysts for this transformation remains important and challenging. In this work, a new sulfonate coordinated Zr(iv ) catalyst was prepared by the coordination of Zr(iv ) onto the sulfonate groups of Amberlyst-15, which can effectively catalyze the MPV reaction and quantitatively convert carbonyl compounds to the corresponding alcohols with high reactivity and stability. Detailed mechanistic investigations reveal that the catalytic performance of Zr-AIER can be attributed to the synergetic effect between Zr 4+ and the sulfonate group, and the porous structure with high surface area.